(untitled) (Research, Society and Development, 2022)
Objective: The objective of this study was to analyze the scientific production on the diagnostic and therapeutic itinerary of people with cancer published in online journals. Methodology: This is a bibliometric study, carried out with eight articles published between 2016 and 2020 in the LILACS, BDENF, MEDLINE databases. Results: The year 2018 had the highest number of publications on the subject, highlighting that 100% of the journals are national and Revista Saúde Pública had the highest impact factor among those found. Discussion: The investigation showed that most of the publications were conducted by researchers in the field of Nursing and Pharmacy, with varying levels of academic degrees. In general, it was observed that publications involving diagnostic and therapeutic itineraries of people with cancer present a biomedical and sociological approach to the experiences attributed to the disease. Conclusion: We believe in the importance of developing other studies, with more robust samples and that describe more details about the access and the diagnostic and therapeutic itinerary of cancer patients.